Novel autoantibodies in rheumatoid arthritis - A.F. Bonifacio; A. Alunno; G.M.C. La Paglia; E. Valentini; M.C. Leone; E. Bartoloni; Roberto Gerli (Reumatismo, 2019)
Rheumatoid factor and antibodies against cyclic citrullinated peptides represent a diagnostic hallmark in rheumatoid arthritis (RA). However, over the last decades many other autoantibodies have been identified. Several proteins can trigger an aberrant autoimmune response in their native form while others acquire this feature after post-translational modifications such as citrullination, carbamylation or acetylation. It is of interest that also the enzymes catalyzing such post-translational modifications (e.g. the protein arginine deiminases) can transform themselves into autoantibodies in RA. The purpose of this review article is to provide an overview of relevant literature published over the last years regarding novel autoantibodies and their possible diagnostic and prognostic significance in RA.